Systemic and mucosal humoral responses to Helicobacter pylori in gastric cancer. - Crabtree, J E (1993)
The systemic IgG response to Helicobacter pylori was examined in 70 patients with gastric cancer. H pylori IgG antibodies were assayed by enzyme linked immunosorbent assay (ELISA), and serological recognition of H pylori antigens was characterised by western blotting. A percentage of 78.5 were seropositive by ELISA. Two of five patients under age 50 were seronegative. Positivity was unrelated to age, sex, tumour type, or site. Ninety one per cent of ELISA positive cancer patients recognised the H pylori cytotoxin associated 120 kilodalton (kD) protein, significantly more than a control group of 47 ELISA positive patients with non-ulcer dyspepsia (72%). Four of 15 ELISA negative cancer patients also showed recognition of this protein in western blots. Mucosal IgA responses to H pylori were examined by immunoblotting supernatants of in vitro cultured resected antral mucosa in an overlapping group of 19 gastric cancer patients. Eighteen had a positive response, including 10 of 11 negative for H pylori by biopsy urease testing. The systemic and local immunoblotting results show that the high seroprevalence of H pylori antibodies detected by ELISA is nevertheless an underestimate of past infection. Dyspepsia screening policies based solely on H pylori ELISA would miss some young patients with gastric cancer. Further study of the relation of the H pylori cytotoxin to gastric precancerous lesions is warranted.